Maternal allergy is associated with surface‐bound IgE on cord blood basophils. Issue 6 (27th August 2013) - Matson, Adam P.; Cloutier, Michelle M.; Dhongade, Ashish; Puddington, Lynn; Rafti, Ektor
Abstract: Background: The cell type(s) mediating the maternal influence on allergic disease in children remain unclear. We set out to define the relationship between maternal allergy and frequencies of cord blood (CB) basophils, and plasmacytoid dendritic cells (pDCs); to characterize surface‐bound IgE and FcεRI expressions on these cells; and to investigate the association between maternal and CB serum IgE levels with surface‐bound IgE and FcεRI expressions. Methods: One hundred and three mother/infant dyads were recruited prenatally, and maternal allergic history was recorded. Maternal blood was collected prior to delivery, and CB was collected after birth. Flow cytometry was used to identify CB basophils and pDCs and to determine surface‐bound IgE and FcεRI expressions. Results: Frequencies of CB basophils and pDCs were low and not related to maternal history of allergy. Percentages of CB basophils with surface‐bound IgE were significantly higher in infants of allergic mothers compared with infants of non‐allergic mothers (median, 59.60% vs. 19.70%, p = 0.01). IgE on CB basophils correlated with CB IgE levels (r = 0.72, p < 0.0001), but not with maternal IgE levels (r = 0.26, p = 0.06). IgE on CB pDCs was low and not significantly associated with maternal or CB IgE levels. Similarly, FcεRI expression by CB basophils and pDCs was not significantly associated with maternal or CB IgE levels. Conclusions: Frequencies of CB basophils and pDCs are not influenced by maternal allergy. CB basophils and pDCs have surface‐bound IgE and express FcεRI; however, only IgE on CB basophils appears influenced by maternal allergy. Abstract :